Ultrasensitive ethanol sensor based on segregated ZnO-In2O3 porous nanosheets - Yan, Wenjun; Chen, Yulong; Zeng, Xiaomin; Wu, Gu; Jiang, Wei; Wei, Di; Ling, Min; Wei Ng, Kar; Qin, Yuxiang (Applied surface science, 2021)
[Display omitted] •Segregated ZnO-In2O3 porous nanosheets are synthesized facilely via one-pot solvothermal method.•The doped Indium stems the porous nanosheets stacking, inducing lots of heterojunctions.•The sensor exhibits superior ethanol sensing behaviors under natural humidity for a long period.•After aging for 10 months, the device shows celerity response to simulated drunken subjects.•This study meets the challenge of repeatably and reliably superior ethanol sensing performance in real world. ZnO nanosheets exhibit notably interesting gas sensing performances due to their great carrier transport and high special surface area. However, not only the 2D nanosheets tend to stack suppressing the surface area, but also the pristine ZnO cannot show desired ethanol sensing properties. Herein, segregated ZnO-In2O3 porous nanosheets are synthesized facilely via one-pot solvothermal method. The Indium doping stems the porous nanosheets stacking, as well as induces lots of heterojunctions. Due to the specific porous structure for high gas accessibility, thickness less than double Debye length, abundant reaction sites and heterojunctions, the segregated ZnO-In2O3 nanosheets exhibit remarkable ethanol sensing performance (LOD of 100 ppb, response/recovery time of 3/8 s, and great repeatability and selectivity under natural humidity for a long period). This study provides a prospect for practical applications of ZnO-In2O3 ethanol sensors.